Analisis Efektivitas Komunikasi Model Prima Tani Sebagai Diseminasi Teknologi Pertanian di Desa Citarik Kabupaten Karawang Jawa Barat - A. Saleh; F. N. Suwanda (Jurnal Komunikasi Pembangunan, 2008)
This research is aiming to know the analyze of Prima Tani model communication effectiveness as a agriculturaltechnology disseminations in Citarik Village, Karawang Region, West Java Province. The analyze was formed to findout personal characteristics, community of farmer institutions, accessibility, essential and support factors inagricultural development, Prima Tani communication media, Prima Tani communication effectiveness in agriculturalbusiness (planting rice) development model. This research was designed as a correlated descriptive survey, and usingcluster random sampling method for 80 farmer respondents. The analyze of correlations were done by rankSpearman and chi-square. The results of research are: age, formal education, non-formal education, farmingexperience, average income, agricultural business status, land usage, interpersonal communication farmingorientations, and farmer status that personal characteristics as an internal factors have a highly significantcorrelation with spread out technology and Prima Tani clinic in usefull of communication media. Spread outtechnology and Prima Tani clinic in usefull of communication media have a significant correlation with externalfactors. The usefull of communication media have a highly significant correlation with Prima Tani communicationeffectiveness in agricultural business development model, except affective. Internal factors have a significantcorrelation to Prima Tani communication effectiveness in agricultural business development model, except affective.External factors have a significant correlation to Prima Tani communication effectiveness in agricultural businessmodel